2008
DOI: 10.1007/s12031-008-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PACAP on the Circadian Changes of Signaling Pathways in Chicken Pinealocytes

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is involved in the regulation of circadian rhythms. In mammals, the brain's biological clock is the suprachiasmatic nucleus, receiving photic information from the retina through the retinohypothalamic pathway, where PACAP is the main cotransmitter of glutamate. The primary conductor of circadian rhythms of birds is the pineal gland. The presence of PACAP has been demonstrated both in the rat and avian pineal gland, where PACAP stimulates melatonin synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…For example, exposure of the chicken pineal gland to PACAP induces a transitory increase in melatonin secretion, but does not cause phase shift of the melatonin rhythm [6466]. PACAP has also been shown to directly influence clock gene expression [67] and affect signalling pathways that integrate the molecular clock in the functionality of circadian rhythms in a dose- and phase-dependent manner [68]. Further studies are needed to determine whether the ADCYAP1 polymorphism exerts its effect on nocturnal migratory restlessness via a phase-shift of the endogenous oscillator(s) or via a modulation of the downstream processes of the molecular clock.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure of the chicken pineal gland to PACAP induces a transitory increase in melatonin secretion, but does not cause phase shift of the melatonin rhythm [6466]. PACAP has also been shown to directly influence clock gene expression [67] and affect signalling pathways that integrate the molecular clock in the functionality of circadian rhythms in a dose- and phase-dependent manner [68]. Further studies are needed to determine whether the ADCYAP1 polymorphism exerts its effect on nocturnal migratory restlessness via a phase-shift of the endogenous oscillator(s) or via a modulation of the downstream processes of the molecular clock.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the effect PACAP could involve the phosphorylation of the p38 MAPK (Racz et al, 2008).…”
Section: Actions Of Pituitary Adenylate Cyclase-activating Polypeptidmentioning
confidence: 99%
“…In spite of the large variety of tissues containing or releasing PACAP, there are only sporadic data about its function in skeletal elements such as bone [7][9]; in particular, its presence in hyaline cartilage has not been reported. PACAP is a multifunctional peptide that can regulate diverse physiological processes such as testicular ageing [10], circadian rhythm [11], brain development [12] or cell migration [13]. PACAP is also regarded as a neurotrophic [14], [15] and anti-inflammatory substance in the CNS [16] and is reported to prevent harmful effects of oxidative stress in various tissues [17][19].…”
Section: Introductionmentioning
confidence: 99%